2014
DOI: 10.1186/1477-7819-12-34
|View full text |Cite
|
Sign up to set email alerts
|

The rising trend of papillary carcinoma in thyroidectomies: 14-years of experience in a referral center of Turkey

Abstract: BackgroundDuring the past 25 years, the incidence of thyroid papillary carcinoma (TPC), especially the micropapillary subtype, has been increasing in different countries worldwide. The rise in the rate of thyroid malignancies were also determined in Turkey in the last two decades. This fact was attributed to the Chernobyl accident because Turkey is one of the affected countries by the radioactive fallout. The aim of this study was to assess the changes in the parameters of the thyroid and put forth the reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
14
1
1
Order By: Relevance
“…12,19,20 Our results are consistent with the international remote and recent data regarding the pattern and frequency of neoplastic diseases of thyroid, including the predominance of papillary carcinoma. Our finding regarding increased trend of papillary carcinoma diagnosis among malignant thyroid tumors is also consistent with that of Yang et al (2013), Yildiz et al (2014) and Amphlett et al (2013). [21][22][23] Follicular adenoma was the commonest benign thyroid neoplasms in our study accounting for 78.18% of benign neoplasms which is in accordance with Ariyibi et al (2013) who found 89.5% cases to be follicular adenomas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12,19,20 Our results are consistent with the international remote and recent data regarding the pattern and frequency of neoplastic diseases of thyroid, including the predominance of papillary carcinoma. Our finding regarding increased trend of papillary carcinoma diagnosis among malignant thyroid tumors is also consistent with that of Yang et al (2013), Yildiz et al (2014) and Amphlett et al (2013). [21][22][23] Follicular adenoma was the commonest benign thyroid neoplasms in our study accounting for 78.18% of benign neoplasms which is in accordance with Ariyibi et al (2013) who found 89.5% cases to be follicular adenomas.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding regarding increased trend of papillary carcinoma diagnosis among malignant thyroid tumors is also consistent with that of Yang et al (2013), Yildiz et al (2014) and Amphlett et al (2013). [21][22][23] Follicular adenoma was the commonest benign thyroid neoplasms in our study accounting for 78.18% of benign neoplasms which is in accordance with Ariyibi et al (2013) who found 89.5% cases to be follicular adenomas. 24…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that among all the pathological types of thyroid cancer, the proportion of papillary carcinoma has risen from 51.55% (50/97) in 1995 to 87.63% (673/768) in 2010. Similarly in a recent study from Turkey, Yildiz et al (2014), report 216 thyroid carcinoma which account for 13.6% of their thyroidectomies and concluded that there is a significant increase in the frequency of papillary and micropapillary carcinoma while comparing their two study periods. Within the KSA, Hussain et al (2013), from Riyadh report that a total of 2292 patients with thyroid cancer were treated from 2000 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Amphlett et al (2013), observed the recent trends in the incidence, geographical distribution, and survival from thyroid cancer in Wales. From Turkey, Veyseller et al (2009), looked into thyroidectomies for benign diseases, while Yildiz et al (2014), studied the rising trends of papillary carcinoma of thyroid. Recent registry based studies are also available from Finland (Hakala et al, 2012) and Switzerland (Rapiti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the frequency of thyroid cancer could be attributable to several different reasons in the case of Turkey: the Chernobyl nuclear accident, mandatory iodization for endemic iodine deficiency, increased diagnostic scrutiny, strict pathologic investigation, and changing surgical techniques. [13] In our study, thyroid cancer is the third most common cancer in females and 11 most common in males. This result is similar to that reported by Baş et al [14] and İzmirli et al [9] and is also consistent with the data of the Turkish Cancer Department (Türkiye Kanser Daire Başkanlığı).…”
Section: Discussionmentioning
confidence: 99%